(untitled) (Research, Society and Development, 2020)
Baru almond is an oilseed native to the Cerrado biome and stands out because of its large nutrient content. The present study sought to perform a centesimal, mineral, microbiological and sensory characterization of food pastes made with different contents of baru almonds: P1 (35%); P2 (17.5%); and P3 (0%). Hazelnuts were used as the control to counterbalance the different percentages of almond. The highest concentrations of moisture, lipids, and calcium and the highest total energy value were observed with the food pastes consisting of 35% baru almond (P1). However, a decrease in ash, protein and carbohydrate contents occurred. Higher concentrations of potassium and zinc were found in the food pastes made with 0% baru almond (P3), indicating that hazelnuts contained a greater quantity of these minerals. As for the microbiological results, no coliforms were found for any of the pastes tested. Low levels of molds and yeasts were observed at the dilutions of 10-1 and 10-2 UFC/g and none at 10-3 UFC/g. For the taste sensorial attributes, global impression and intention to purchase, no significant differences were observed between the formulations. However, the food pastes consisting of 17.5% baru almond and 17.5% hazelnut (P2) received the highest scores for appearance and texture. It is concluded that the food pastes made with different contents of baru almond had satisfactory nutritional, sensory and microbiological characteristics for consumption.